INTEGRATED DECISION ANALYSIS PROCESS FOR SELECTING GAS OPTIMIZATION ALTERNATIVES; STUDY CASE OF X AND Y FIELDS, PT CHEVRON PACIFIC INDONESIA - NAZAMZI 29115220 , ARDI
Asset Gas Team is responsible for maintaining and increasing gas production in PT. Chevron Pacific Indonesia (CPI) concession area. One of the initiative for increasing production is to utilize idle gas opportunities within existing X and Y Oil Fields. These gas opportunities had been identified based on subsurface data so the project team confidence that gas is presence in reservoir and confirm by early production tests. The main issues of developing the gas opportunities are due to the gas opportunities size is small-medium and the distance of X and Y Fields to nearest surface gas facility at about 10 Km. Optimization efforts for idle gas opportunities at X and Y Fields will follow PT CPI project management standard process. Optimization Team had been pass Stage-1 of identifying opportunities and now is moving to Stage-2 for generating and selecting alternatives. The objectives of this final project are assessing all possible gas production alternatives that might applicable at X and Y Fields and then choose the preferred gas production alternative to be further develop. The scope of final project work will be subsurface works at project management Stage-2 as basis for further Stage-3 work. The methodology of final project work will combine existing Quantitative analyses of PT CPI decision analysis standard with Qualitative analysis and Analytical Hierarchy Process (AHP) analysis. Qualitative and Quantitative analysis will be conducted at parallel and the outputs of these analysis will be used to develop integrated AHP analysis. Quantitative analysis will cover validation of resource volume estimation, project uncertainty and risk management plans, economic calculation, decision tree and value of information (VOI). Qualitative content analysis will be used to analyze semi-structured interview result of leader representatives for Opex (operation expenditure) allocation and expectation for successful project. AHP will be the final analysis to get final recommendation. Three gas optimization alternatives; CTG (Convert to Gas), local electricity and gas dumpflood, have been analyzed to be implement in X and Y Fields. AHP analysis final result suggest that local electricity is the appropriate alternative to be implemented for detail engineering and economic analysis in Stage3 project management process. Local electricity alternative process gas at field location and produce electricity to support oil wells operation at X and Y Fields. CTG alternative not consider as good alternative since it required high investment on building gas pipeline to connect gas wells to nearest facility. Gas dumpflood is a not suitable for X and Y Fields due to low confidence on chance of success based on expert technical judgement. Integrated decision analysis flow process which consists of Quantitative analyses, Qualitative analysis and AHP analysis is highly recommended to be implement at Asset Gas Team to analyze other gas opportunities optimization.